Study of the mutation causing type 1 polysaccharide storage myopathy in a Mangalarga Marchador population used in breeding programs - da Silva, Nayne Vieira (2023)
The Mangalarga Marchador (MM) breed, which originated in Brazil, constitutes the largest number of horses in the country. The animals are versatile and used in several sports because of major investments made for the genetic improvement of the breed. In recent decades, advances in molecular techniques enabled the identification of genetic diseases in horses. Conducting molecular tests and determining the occurrence of mutations are fundamental for the early identification and prevention of abnormalities. Among the known genetic diseases that occur in horses, the c.926G>A mutation in the GYS1 gene that causes type 1 polysaccharide storage myopathy (PSSM1) stands out, because it has been identified in several breeds of horses. Although myopathy is common in MM horses, the occurrence of the c.926G>A mutation in the GYS1 gene has not yet been evaluated. The lack of knowledge about the possible presence of PSSM1 averts the adoption of control measures to prevent the spread of the disease in MM horses. Therefore, the aim of this study was to verify the occurrence of the mutation that causes PSSM1 in MM horses used in breeding programs. Blood DNA was extracted and the region of the GYS1 gene containing the mutation was amplified and sequenced. No mutation in the GYS1 gene was found in the evaluated samples. However, since clinical signs of myopathy are frequently observed in MM horses, further studies, including histological analysis, are necessary to establish the underlying causes. In addition, if there is a genetic pattern of occurrence, molecular studies should be considered.